Chick early amniotic fluid component improves heart function and protects against inflammation after myocardial infarction in mice - Wang, Juan; Chen, Xiejiu; Zhang, Lihong; Zheng, Yufan; Qian, Jin; Sun, Ning; Ding, Xiaolei; Cui, Baiping (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction (MI) is the major cause of mortality around the world. We recently demonstrated that chick early amniotic fluid (ceAF) can effectively rescue ischemic heart injury, indicating that it has a therapeutic function in MI. However, its functional components and the underlying mechanisms remain to be clarified. Here, we demonstrated that a fraction of ceAF, peak 8 (P8), had a protective effect on acute MI. P8 significantly decreased cardiomyocyte cross-sectional areas and cardiomyocyte apoptosis in MI mice. Using a human embryonic stem cell-derived cardiomyocyte model, which was subjected to hypoxia and reoxygenation, mimicking MI state, we found that P8 treatment reduced apoptosis and reversed myocardial contractility. Mechanistically, P8 improved cardiac function by inhibiting NF-κB signaling and downregulating inflammatory cytokine expression. Using mass spectrometry, we identified that guanosine and deoxynucleoside were the main functional components of P8 that suppressed the inflammatory response in human embryonic stem cell-derived cardiomyocytes. Collectively, our data suggest that specific components from ceAF are promising therapeutic agents for ischemic heart injury and could be a potential supplement to current medications for MI.